On the Origin of Pupa Sabiak - Zou, P. Hoideiniang (Journal of religious and theological information, 2025)
This study delves into the rich cultural heritage of the Zomis, exploring the intricate relationship between their animistic beliefs and the natural environment. The “Pupa Sabiak” belief system, which reveres spirits, deities, and ancestors embodied in the landscape, is examined in depth. This investigation elucidates the fundamental principles of Zo animism, showcasing its profound respect for the natural world, spirits, and the interplay between the material and paranormal realms. Rituals, such as the “Sakhua” celebration, are scrutinized, revealing joyous processions, dances, and offerings made to honor the land and wood spirits. The animistic framework highlights the significance of offerings and sacrifices in Zomi ceremonies, aimed at harmonizing the spiritual and human domains. This research underscores the enduring value of animism in the Zo community, preserving a rich cultural legacy and robust spiritual identity. Furthermore, it aligns with philosophical models of recorded animistic practices, providing a fertile ground for discussion and intellectual exploration.